Intestinal Barrier Damage and Growth Retardation Caused by Exposure to Polystyrene Nanoplastics Through Lactation Milk in Developing Mice - Chaoyu Zhou; Haiyan Wu; Lei Zhang; Xiao Xiao; Xiaodan Wang; Mingju Li; Runqiu Cai; Jia You; Qi Chen; Yifei Yang; Xinyuan Tian; Qianyu Bai; et al. (Nanomaterials)
Microplastics, defined as plastic fragments smaller than 5 mm, degrade from larger pollutants, with nanoscale microplastic particles presenting significant biological interactions. This study investigates the toxic effects of polystyrene nanoplastics (PS-NPs) on juvenile mice, which were exposed through lactation milk and drinking water at concentrations of 0.01 mg/mL, 0.1 mg/mL, and 1 mg/mL. The results show that PS-NP exposure during lactation and juvenile periods caused delayed weight gain and impaired organ development, particularly in the liver and kidneys, without causing functional abnormalities or toxic injuries. The primary toxicity of PS-NPs was observed in the intestinal tract, including shortened villi, disrupted tight junctions, inhibited epithelial cell proliferation, and oxidative stress responses. These findings highlight the importance of evaluating the developmental toxicity of nanoplastics at environmentally relevant doses.